Hubungan Pajanan Pestisida dengan Gangguan Keseimbangan Tubuh Petani Hortikultura di Kecamatan Ngablak Kabupaten Magelang - Samosir, Kholilah; Setiani, Onny; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2017)
Latar belakang, Upaya untuk meningkatkan produksi pertanian agar tanaman tidak rusak oleh hama dan penyakit petani menggunakan pestisida dengan harapan mampu meningkatkan hasil pertanian dan serta dapat membuat biaya pengelolaan pertanian menjadi lebih efisien dan ekonomis. Pestisida dapat bersifat akut, kronis maupun sistemik, yang dapat menyerang sistem syaraf ,salah satunya gangguan keseimbangan,hati atau liver,dan keseimbangan hormonal dengan cara mempengaruhi kerja enzim. Penelitian bertujuan mengetahui hubungan pajanan pestisida dengan gangguan keseimbangan tubuh pada petani hortikultura di Kecamatan Ngablak, Kabupaten Magelang.Metode, penelitian ini merupakan penelitian observasional dengan desain Cross Sectional. Populasi penelitan adalah petani yang termasuk dalam kelompok tani desa Sumberejo. Sampel adalah petani desa Sumberejo yang memenuhi kriteria sebanyak 70 responden. Pengumpulan data menggunakan kuisioner, pemeriksaan kolinesterase dalam darah menggunakan Spectrophotometer, dan gangguan keseimbangan tubuh dengan menggunakan romberg test.Hasil, Sebanyak 14,3 % petani dari hasil pemeriksaan kadar kolinesterase pada petani desa Sumberejo di Kecamatan Ngablak mengalami keracunan pestisida dan 34,3% petani dari hasil pemeriksaan romberg test mengalami gangguan keseimbangan, dari hasil uji chi square menunjukkan ada hubungan antara masa kerja nilai (p = 0,036),lama kerja per hari (p = 0,015), penggunaan alat pelindung diri (p = 0,035 dan kadar kolinesterase (p = 0,000 dengan gangguan keseimbangan dan tidak ada hubungan antara frekuensi, jumlah, jenis, dosis, cara penyemprotan, dan pengelolaan pestisida dengan gangguan keseimbangan tubuhKesimpulan, faktor risiko masa kerja petani, lama kerja per hari,cara penyemprotan, penggunaan alat pelindung diri mempengaruhi adanya kadar kolinesterase dalam darah yang dapat menyebabkan gangguan keseimbangan tubuh. ABSTRACTBackground: Efforts to increase agricultural production to prevent damage or plant from past and deseae are using pesticides. It is expected to increase the agricultural yields and also can make the cost of management cheaper and economical. The pesticide give rice to cause acute, chronic or systemic poisoning. Pesticides can attack nervous system, and cause body balance disorder, The liver disorder, stomach, the immune system and the hormonal balance affect the action of enzyme. The purpose of this research was to the assocation between the pesticide exposure and body balance disorders on horticultura farmers in Ngablak sub district, Magelang District.The method: This research used the observational analiytic method with cross-sectional approach. The population in this research were horticultura farmers of Sumberejo village. The sample in this research were farmers that meet the inclusion criteria. Data collection used the questionnaire, cholinesterase in blood by spectrophotometer, examination the body were disorder was measured by the romberg test. The number of samples in this research ballance 70 farmer in Ngablak sub district, Magelang District.The results: The average level of cholinesterase of the farmer at Sumberejo village in Ngablak sub-district showered that 14,3% were poisoned by pesticide. The study result showed that 34,3% horticultura farmer at Ngablak sub-district suffered ao body balance disorder. Based on chi-square test it showed a assocation between the working period (=0,036), the duration day of work (p=0,015), the personal protective aquipment (p=0,035), the average level of cholinesterase (p=0,000) balance disorders and there is no relationship between the number, type, management, frequency and dose of pesticide spraying with body.The conclusion: Of this research, risk factor of the farmer’s working, the length of work, the spraying method, personal protective equipment effect the avarage level of cholinesterae in blood can cause distrurbance of body balance horticultura farmers.